Characterization of electrospun poly(lactide) composites containing multiwalled carbon nanotubes - Ristić, Ivan; Miletić, Aleksandra; Vukić, Nevena; Marinović-Cincović, Milena; Smits, Krisjanis; Cakić, Suzana; Pilić, Branka (SAGE Publications Inc., 2019)
The main aim of this work was to obtain conductive polymer-based materials by incorporation of different amounts of multiwalled carbon nanotubes (MWCNTs) into poly(lactide)(PLA) using the electrospinning technique. Fiber-based nonwovens with 0.2, 0.5, 1, and 3 wt% of MWCNTs were characterized regarding conductivity, morphology, thermal, and mechanical properties. It was confirmed that an increase of the MWCNTs content does not influence the increase of the material conductivity, since the conductivity was 170 ohm sq−1 for all composites. Scanning electron microscopy and transmission electron microscopy analyses revealed that smooth and beadless fibers were obtained, but also average diameters of composite nanofibers decreased with the increase of the MWCNTs content. Differential scanning calorimetry analysis showed that the presence of MWCNTs in the PLA matrix had a significant influence on the crystallization behavior of PLA nanofibers, because the decrease in crystallization temperature (Tc) was detected. Also, the incorporation of MWCNTs into PLA fibers affected the melting process, enabling the generation of α′ form, while had no influence on ordered α crystal. The enthalpy of composite degradation decreased, because MWCNTs are well-known for good heat conductivity, and with that the second step of degradation slowed down, as it was confirmed by thermogravimetric analysis. The addition of MWCNTs improved mechanical properties of composite fibers and caused the increase of both elasticity and tensile strengths of nanofibers.
The author(s) disclosed receipt of the following financial support for the research, authorship, and/or publication of this article: The authors would like to thank the Ministry of Education, Science and Technological Development, Republic of Serbia, for funding projects III45022 and 172056 and European Cooperation in Science and Technology (COST) action CA15107.
Keywords: Research Subject Categories::NATURAL SCIENCES:Physics; Poly(lactide) nanofibers; multiwalled carbon nanotubes; electrospinning; conductive polymer; thermal properties